2015
DOI: 10.1002/14651858.cd010907.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to facilitate shared decision making to address antibiotic use for acute respiratory infections in primary care

Abstract: Interventions that aim to facilitate shared decision making reduce antibiotic prescribing in primary care in the short term. Effects on longer-term rates of prescribing are uncertain and more evidence is needed to determine how any sustained reduction in antibiotic prescribing affects hospital admission, pneumonia and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 51 publications
8
134
1
10
Order By: Relevance
“…8 This contrasts with practice in the Netherlands, where 22.5% of RTI episodes in 2010 were treated with antibiotics. 9 A considerable amount of research has been done [10][11][12] to develop interventions that might help general practitioners to reduce the rate of antibiotic prescribing for RTIs. This has been translated into policy guidance 3 and public campaigns 13 to control unnecessary antibiotic use.…”
Section: What This Study Addsmentioning
confidence: 99%
“…8 This contrasts with practice in the Netherlands, where 22.5% of RTI episodes in 2010 were treated with antibiotics. 9 A considerable amount of research has been done [10][11][12] to develop interventions that might help general practitioners to reduce the rate of antibiotic prescribing for RTIs. This has been translated into policy guidance 3 and public campaigns 13 to control unnecessary antibiotic use.…”
Section: What This Study Addsmentioning
confidence: 99%
“…These findings suggests opportunities for improving acute respiratory infection visits by adopting shared decision making, in which the options (using or not using antibiotics) and the benefits and harms of each are explained; parents' concerns, beliefs, expectations, and preferences are explored; and a decision is reached collaboratively. 35 Shared decision making is an effective strategy for reducing antibiotic prescribing for acute respiratory infections in primary care, 36 but widespread implementation is limited. This study found most parents wanted to be involved in these decisions.…”
mentioning
confidence: 99%
“…Esta sazonalidade pode estar superestimada pelo fato de que, nessas épocas do ano, as sintomatologias comuns das morbidades alérgicas e virais podem acarretar prescrição precipitada de antibacterianos (22).…”
Section: Resultsunclassified